A study on a novel piezoelectric bricks made of double-storey piezoelectric coupled beams. (1st July 2022) - Xie, Xiangdong; Wang, Zijing; Zhang, Jiankun; Zhao, Yan; Du, Guofeng; Luo, Mingzhang; Lei, Ming
Abstract: In order to explore more efficient and economical method to harvest footstep energy, a double-storey piezoelectric coupled beam (DPCB) and a corresponding piezoelectric brick are developed. The design of the DPCB makes the piezoelectric patches bonded on its piezoelectric coupled segments (PCSs) to be efficiently used for their uniform surface strain in the vibration process. Two piezoelectric brick specimens are customized, and the influences of a variety of design parameters on the peak-to-peak (pp) voltages/average powers of the piezoelectric bricks are studied by experiment and simulation methods. The research results show that the average power (power density) from PCS1 and PCS2 can reach up to 108.9 mW (43.6 μW/mm 3 ) and 110.9 mW (44.4 μW/mm 3 ) for a piezoelectric patch with a dimensions of 50 mm × 50 mm × 1 mm. This research provided a new footstep harvesting device which has a good application prospect for its high energy harvesting efficiency and cost-effectiveness. At the same time, a series of practical and instructive conclusions are obtained for instruction and application of the new proposed DPCB and piezoelectric brick. Highlights: Two pairs of distinctive Double-layer piezoelectric coupled beams (DPCBs) with high efficiency are proposed. The substrate thickness in PCS2 of DPCB has a notably effect on the electric output of PCSs of DPCB. The optimal load resistance matching the piezoelectric patch of the PCB increases with the increase of the PCB rigidity. An average power of 110.9 mW (44.4 μW/mm 3 ) is achieved from a piezoelectric patch (50 mm × 50 mm × 1 mm) of DPCB.